IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS TEKNOLOGI ARTIFICIAL INTELLIGENSI - Mira Rahmayanti; Samsidar Samsidar; Rosmaimuna Siregar; Thofik Hidayat; Jarki Ramadhan (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study examines the implementation of Islamic Religious Education (PAI) based on Artificial Intelligence (AI) learning at SMA Negeri 5 Padangsidimpuan. With a qualitative approach, this study analyzes school readiness in terms of infrastructure, human resources, policies, and the use of AI applications such as Canva, Puzzle Maker, and Google Classroom in PAI learning. The results show that schools already have basic infrastructure (bandwidth of 100 Mbps) and teachers with adequate digital literacy, although AI adoption still varies. Key challenges include budget constraints, lack of operational guidance, and the need to supervise the use of students' gadgets. This research makes an academic contribution as a pioneering study on the integration of AI in high school level PAI in developing regions, while offering practical recommendations for strengthening teacher training, school policies, and collaboration with stakeholders. The findings of the study underscore the potential of AI in improving the quality of interactive and contextual PAI learning, without neglecting Islamic values.